Hunchback : a novel - Ichikawa, Saō, 1979- (Hogarth, 2025)
"Born with a congenital muscle disorder, Shaka spends her days in her room in a care home outside Tokyo, relying on an electric wheelchair to get around and a ventilator to breathe. But if Shaka's physical life is limited, her quick, mischievous mind has no boundaries: she takes e-learning courses on her iPad, publishes explicit fantasies on websites, and anonymously troll-tweets to see if anyone is paying attention ("If I were to live again, I'd want to be a highclass prostitute"). One day, she tweets into the void an offer of an enormous sum of money for a sperm donor. To her surprise - and ours - her new nurse accepts the dare, unleashing a series of events that will forever change Shaka's sense of herself as a woman in the world. Hunchback has shaken Japanese literary culture with its skillful depiction of the physical body and unrepentant humor. Winner of the prestigious Akutagawa Prize, it's a feminist story about the dignity of an individual who insists on her right to make choices for herself, no matter the consequences. Formally creative and refreshingly unsentimental, Hunchback depicts the joy, anger, and desires of a woman demanding autonomy in a world that doesn't always always grant it to people like her. Full of wit, bite, and heart, this unforgettable novel reminds us all of the full potential of our lives, no matter the limitations we experience"--